Peran Kepuasan Pelanggan Dalam Mediasi Pengaruh Kualitas Pelayanan Dan Discount Terhadap Impulse Buying Pelanggan Toko Sepatu Stars - Purba, Rido; Sinaga, M. Arian L.; Sarwoto, Sarwoto; Cen, Cia Cai (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2024)
This research uses approach study quantitative with type study purposeful explanatory research For analyze How connection between One variable with variable other . Population in this research is customer Stars Tebing Tinggi Shoe shop , numbering 96 people. Tools analysis : validity test, test reliability, statistical t test and indirect effect test with use Smart tools PLS 3.0.Results of this research shows that quality service influential significant to satisfaction customers , discounts influential to satisfaction customers, quality service influential against impulse buying , discounts influential to impulse buying , satisfaction settlement influential to impulse buying , and quality service as well as influence discount to satisfaction customer as intervening variable.